Effect of cigarette smoking on the bond strength between resin cement and dental CAD/CAM ceramics. Issue 21 (2nd November 2017) - Tsai, Mei Mei; Qiao, Wei; Tsoi, James Kit Hon; Della Bona, Alvaro; Matinlinna, Jukka Pekka
Abstract: Although the effects of cigarette smoking on several dental problems have been widely studied, the association between tobacco exposure and resin-ceramic bonding is rarely reported. This study investigated the resin-ceramic adhesion (shear bond strength, SBS) and associated risk factors on three selected dental CAD/CAM ceramics using a novel model to simulate the exposure to cigarette smoking. Specimens from IPS e.max® CAD, Vitabloc® Mark II for Cerec and Zirconia Cercon were prepared and treated using silicacoating and silane. A layer of resin cement was applied on the treated ceramic surfaces and light activated. Specimens were placed in a chamber and challenged with various numbers of cigarettes (0, 1, 5, 10, and 15). Then, the specimens were subjected to SBS test and fractured surfaces were examined using scanning electron microscopy (SEM) and energy-dispersive X-ray spectrometry (EDX) to determine the failure mode and surface composition. Overall, the mean SBS of IPS e.max ® CAD (9.6 ± 3.4 MPa), Vitabloc ® Mark II for Cerec (9.3 ± 2.5 MPa) and Zirconia Cercon (8.7 ± 3.0 MPa) did not show any statistical significant difference ( p = 0.192 > 0.05), such that the adhesion of resin bonded to glass-based ceramics (IPS e.max® CAD and Vitabloc® Mark II for Cerec) decreased with cigarette smoke exposure, but increased for the resin bonded to zirconia ceramic (Zirconia Cercon). Furthermore, the number of cigarettes has a statistically significant effect on the SBS ( p = 0.001), such that in general 5 cigarettes yielded the lowest mean SBS (7.6 ± 2.1 MPa). SEM-EDX analyses showed mostly adhesive failures in all experimental groups with changes in surface morphology and chemical composition after smoking challenge. Cigarette smoking produces a different effect on resin-ceramic bonding depending on ceramic type that may be due to chemical reactions in the bonding interface and changes in temperature and moisture. Further work should explore the mechanism to which cigarette smoke affects the resin-ceramic bonding and its clinical relevance.